1971
DOI: 10.1111/eci.1971.1.4.248
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Triglycerides, Phospholipids and Glycogen in Skeletal Muscle and of Free Fatty Acids and β‐Hydroxybutyric Acid in Blood in Man in Response to Exercise

Abstract: Twenty‐four fasting male subjects exercised until exhaustion on a bicycle at a relative workload of about 70% of the workload at heart rate 170 per min. Muscle tissue was obtained by needle biopsy from the lateral femoral muscle before and after exercise.—The average work time was 99 min. The muscle triglyceride concentration decreased during the exercise from 10.4 to 7.8 μmoles per gram and that of glycogen from 10.4 to 3.4 mg per gram. The concentration of phospholipids in the muscle remained unchanged.‐The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
58
3

Year Published

1980
1980
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(64 citation statements)
references
References 22 publications
3
58
3
Order By: Relevance
“…Since in normal subjects serum insulin usually decreases during more prolonged exercise [16,38,39], no additional carbohydrate was offered to them during the ergometer test. Nevertheless, muscle triglycerides on average did not decrease during exercise in the normals, in contrast to the findings of Carlson et al, who studied fasting healthy volunteers at a maximal work load [40]. It is likely that the ingestion of a carbohydrate breakfast has modified our results to some degree, although it has been indicated previously that only 10 to 15% of 100 g orally administered glucose become available to peripheral tissues within the first 2 hours, the major part being retained in liver [15]; the percentage of glucose released from liver is only moderately larger when the same amount of glucose is ingested during exercise [15,41].…”
Section: Discussioncontrasting
confidence: 97%
“…Since in normal subjects serum insulin usually decreases during more prolonged exercise [16,38,39], no additional carbohydrate was offered to them during the ergometer test. Nevertheless, muscle triglycerides on average did not decrease during exercise in the normals, in contrast to the findings of Carlson et al, who studied fasting healthy volunteers at a maximal work load [40]. It is likely that the ingestion of a carbohydrate breakfast has modified our results to some degree, although it has been indicated previously that only 10 to 15% of 100 g orally administered glucose become available to peripheral tissues within the first 2 hours, the major part being retained in liver [15]; the percentage of glucose released from liver is only moderately larger when the same amount of glucose is ingested during exercise [15,41].…”
Section: Discussioncontrasting
confidence: 97%
“…A major novel finding in the present study was that female subjects, regardless of training status, utilized a significant amount of MCTG during prolonged exercise, whereas male subjects did not. The fact that male subjects did not utilize MCTG during exercise to any measurable extent is in accord with our (22,25) previous findings as well as other studies (1,12,21,44) but does contrast with some studies (4,19,34) in which MCTG utilization was determined by applying the muscle biopsy technique. In recent studies (17,38) in females in which a combination of isotope tracer technique and indirect calorimetry was used, it was suggested that the additional source of fatty acids oxidized during exercise at the same absolute workload after training (vs. before training) was provided by MCTG.…”
Section: Discussionsupporting
confidence: 92%
“…In studies (27,37) using stable isotope techniques combined with indirect calorimetry, it was estimated that MCTG accounted for 20-25% of the oxidative metabolism during submaximal exercise. However, when direct measurements of MCTG concentration in muscle biopsies have been used, some studies (4,19,34) have found a decrease in MCTG concentration during submaximal exercise, whereas others (1,21,22,25,44) have observed no change. In all of the above-mentioned studies, only male subjects have participated.…”
mentioning
confidence: 99%
“…This confirms conclusions from stable isotope studies reporting that ϳ50% of total fat oxidation is accounted for by plasma FFA oxidation, suggesting that other substrate sources like IMTG play a substantial role in energy provision during exercise (22,38,45,55). However, as noted in the introduction, the importance of IMTG stores as a substrate source has been disputed as some (4,11,13,17,20,25,42,56), but certainly not all, studies (3,21,30,31,44,49,50,58) using the biochemical triglyceride extraction method on muscle samples collected before and after exercise have been able to show a significant decline in IMTG content after prolonged endurance exercise. The apparent controversy, elegantly described by Watt et al (57), can be explained partly by the marked between-biopsy variability (ϳ24%) that has been reported when this technique (58) is used.…”
Section: Discussionsupporting
confidence: 82%